Gastric Bypass Surgery Leads to Long-term Remission or Improvement of Type 2 Diabetes and Significant Decrease of Microvascular and Macrovascular Complications. Issue 6 (June 2016) - Chen, Yijun; Corsino, Leonor; Shantavasinkul, Prapimporn Chattranukulchai; Grant, John; Portenier, Dana; Ding, Laura; Torquati, Alfonso
Abstract : Objectives: The aim of the study was to compare long-term outcomes of 2 groups of morbidly obese patients with type 2 diabetes mellitus—1 managed by Roux-en-Y gastric bypass surgery and a comparable group managed medically. Methods: The present study was a single-institution retrospective study. Of the 173 obese patients with type 2 diabetes mellitus undergoing gastric bypass surgery between January 2000 and July 2004, 78 patients (45%) were followed for at least 10 years. The control group consisted of 80 diabetic obese patients from the same period with similar body mass index, age, race, and severity of diabetes. The median follow-up was 11 years for both the groups. Results: The group undergoing gastric bypass surgery had greater percentage of excess weight loss than the control group—66% versus −1.6%, respectively. Forty-one patients (52.6%) in the surgery group had complete remission of diabetes and 5 (6.4%) had partial remission. Twelve patients (15.4%) had diabetes recurrence after initial remission. No patient in the control group had remission of diabetes. Compared with the control group, the group undergoing gastric bypass surgery had a significantly reduced incidence of microvascular complications—46.3% versus 11.5%, and macrovascular complications—20.3% versus 5%, respectively ( P < 0.01). Conclusions: In this study, we demonstrated that after 10 years of follow-up, Roux-en-Y gastric bypass surgery, compared with nonsurgical medical management, resulted in significantly greater weight loss, reduction in hemoglobin A1c, and use of antidiabetic medications, and very importantly a lower incidence of both microvascular and macrovascular complications in obese patients with type 2 diabetes.